Pentahelix Model Collaboration In Shaping The Independence of Vagrants and Beggars - Ropiah, Eva; Renata, Alma; Wulandari, Sri; Haryo Bharoto, Raden Mahendra (Pelopor Publikasi Akademika, 2024)
This research aims to analyze the collaboration of the pentahelix model in forming the independence of homeless people and beggars. Cirebon City Regional Regulation Number 13 of 2019 concerning the Implementation of Public Order and Community Peace was issued to tackle homeless people and beggars in Cirebon City but its implementation is not yet optimal. The method used in this research is a qualitative method with data collection techniques, interviews, observation and documentation. The theory used is the theory of collaborative governance by (Ansell and Gash, 2008)